Providing effective feedback to your students / Mazlina Suhaimi - Suhaimi, Mazlina (2004)
This paper discussed the issues in providing effective feedback to students, in general. Issues like students' acceptance, understanding and readiness to change are very important in ensuring the effectiveness in providing feedback while keeping things in perspective. Lecturers or instructors must take serious attention and consideration in the course of proving feedback to identify areas where students can improve their performance as well as prepare themselves for future opportunities.